Neurobehavioural challenges experienced by HIV exposed infants: a study in South Africa - Gina Rencken; Pragashnie Govender; Catharina J. E. Uys (BMC, 2022)
Abstract Background The newborn infant is a complexly organized, competent being, who plays an active role in shaping their environment through their increasing skills in autonomic regulation, motor control, regulation of state and social interaction. Infants born to HIV positive mothers, are exposed to HIV and antiretroviral therapy inutero, and may experience adverse effects from this. Methods A cross-sectional study of 132 mother-infant dyads from a large public health hospital in South Africa. Infants were assessed using the Neonatal Behavioural Assessment Scale on day two of life, and mothers mental health assessed using the Edinburugh Postnatal Depression Scale. Medical and demographic data on mothers and infants was collected, including maternal age, HIV status, length of time on antiretrovirals, relationship status, employment status, gravid status, mode of delivery, infant anthropometrics and infant gender. Data was input into IBM SPSS statistics 21, where frequencies and percentages for descriptive analysis, and Chi-square and student's two sample t-tests were run to compare data from HIV infected-exposed and HIV uninfected-unexposed mothers and infants. Results HIV exposed infants were smaller than HIV unexposed infants, even though low birth weight was an exclusion criteria. Statistically significant differences were found between HIV exposed and unexposed infants in neurobehavioiral items of social interaction (p = 0.00), motor system (p = 0.00) and state organization (p = 0.01), with HIV exposed infants performing less optimally in these domains. HIV exposed infants also presented with more abnormal reflexes. Infants born to depressed mothers showed superior motor skills, state organization and state regulation than infants born to mothers who did not score in the possibly depressed range. Conclusions HIV exposed infants have inferior neurobehavioural functioning, which may affect their quality of life and ability to develop a reciprocal relationship with a primary caregiver. This may have an effect on development, behaviour and mental health in later childhood. HIV exposed infants shoud be monitored closely and their functioning in autonomic stability, motor control, resualtion of state and social interaction assessed regularly. Guidance for caregivers in incorporating strategies into the care of these infants is essential to buffer the possible long term negative effects on development.